Bangladesh - China Political Relations: Security Implications for India - Chaudhary, Seema (International Journal of Engineering and Management Research, 2020)
Political relations are a sign of a long-standing, all-encompassing bilateral relationship between two nations. China's increasing involvement in Bangladesh might have both beneficial and harmful effects. China and Bangladesh have had fruitful, long-standing relations since 1975, which have only grown stronger over time. India and the South Asian area are affected by the developing ties between China and Bangladesh. Beijing's notable strengthening of relations with Bangladesh must be seen in the perspective of China's gradual rise to prominence in South Asia since the start of the Belt and Road program. China sees this as a chance to extend its strategic influence into the Indian Ocean region, outside of its usual sphere of influence. The growing Bangladesh-China relations have implications for South Asian region in general and India in particular. Despite India's strategic grievances, Bangladesh has improved its ties with China. However, China has become one of the most reliable sources of armaments and has shown itself to be a helpful counterbalance to India in this area. Bangladesh's military governments were eager to strengthen their strategic ties with China. They had two goals in mind: to dispel the fear of India and to get support and aid from the former. However, China was also eager to acquire strategic control over Bangladesh. China's strategic interests were not served by the 1971 split of Pakistan. China therefore seized the chance to forge closer ties with Bangladesh in 1975 when the country's circumstances shifted against India's interests.